The miR-122 inhibition alleviates lipid accumulation and inflammation in NAFLD cell model. (3rd September 2021) - Hu, Yiyi; Du, Guoping; Li, Guohua; Peng, Xuetao; Zhang, Zhiqiao; Zhai, Yingji
Abstract: Background: Accumulating evidence showed that the expression of miR-122 was abnormal in NAFLD patients; however, the role of miR-122 on lipid accumulation and inflammation in NAFLD is not clear. Methods: RT-qPCR was applied to detect the expression levels of miR-122 and pro-inflammatory cytokines following transfected with miR-122 inhibitor or treated with oleic acid (OA). Detection of lipid accumulation was performed by triglyceride content test and oil red o staining assay. Western blotting was applied to detect the protein levels of TLR7, TLR4, MyD88 and NF-κBp65. Results: We found that the OA promoted lipid accumulation and pro-inflammatory cytokines secretion and activated TLR4/MyD88/NF-κBp65 signalling pathway, which were restored following transfected with miR-122 inhibitor. Conclusions: These results suggested that miR-122 inhibition alleviates lipid accumulation and inflammation in L02 cell induced by OA may through inhibiting TLR4/MyD88/NF-κBp65 signalling pathway. The protective mechanism of miR-122 inhibition in NAFLD must be explored in future studies.